Grading of moyamoya disease allows stratification for postoperative ischemia in bilateral revascularization surgery - Czabanka, Marcus Alexander; Schmiedek, Peter (Acta neurochirurgica, 2016)
BackgroundMoyamoya disease (MMD) may be graded based on DSA, the presence of ischemia in MRI and cerebrovascular reserve capacity allowing the prediction of ischemic symptoms in patients. Cerebral ischemia represents a severe complication in revascularization surgery. Focusing on different clinical features of hemodynamic impairment, MMD grading may allow prediction of ischemic complications. It was the aim to analyze whether MMD grading stratifies for ischemic complications in revascularization surgery for MMD.MethodIn 37 MMD patients a bilateral, standardized, one-staged revascularization approach consisting of STA-MCA bypass/encephalomyosynangiosis (EMS) and single EMS on the contralateral hemisphere was performed. Clinical data including DSA, MRI and rCBF (Xenon-CT) studies were assessed and used for grading MMD. All patients were observed on the ICU for at least 24 h and received CT imaging on the first postoperative day and in case of neurological deterioration. Ischemic complications were analyzed until the day of discharge and at 6-month follow-up.ResultsGrading of MMD revealed 11 hemispheres (15 %) as grade I, 33 hemispheres (44 %) as grade II and 30 hemispheres (41 %) as grade III. Eight ischemic complications were observed (11 %). MMD grading demonstrated a significant correlation with ischemic complications: 0 complications in grade I, 3 in grade II (9 %) and 5 in grade III hemispheres (16 %; p < 0.05, Fisher’s exact test).ConclusionsThe proposed grading system allows to stratify for ischemic complications in MMD patients that receive bilateral, one-staged revascularization surgery. Future studies will have to investigate its use for predicting ischemic complications in other revascularization strategies for MMD.
Gesehen am 04.07.2019